Structural and Optical Properties of Ultra-high Pure Hot Water Processed Ga2O3 Thin Film - Subramani, Shanmugan; Devarajan, Mutharasu (Springer Verlag (Germany), 2016)
Thin film based gas sensor is an advanced application of thin film especially Ga2O3 (GO) thin film gas sensor is useful for high temperature gas sensor. The effect of moisture or environment on thin film properties has more influence on gas sensing properties. Radio Frequency sputtered Ga2O3 thin film was synthesized and processed in ultra-high pure hot water at 95